Facilitating successful implementation of the carer support needs assessment tool (CSNAT) intervention within palliative care. Issue 3 (1st September 2016) - Diffin, Janet; Ewing, Gail; Grande, Gunn
Abstract : Background: The Carer Support Needs Assessment Tool (CSNAT) intervention identifies and addresses family carer support needs towards end of life. 1–3 This person-centred approach involves a change in practice from a practitioner- to carer-led assessment process. Numerous policies recommend carers' needs should be addressed yet there is little guidance on how to achieve this within palliative care. To address this gap and assist a change to a carer-led process, an implementation strategy for the CSNAT intervention was developed, of which facilitation is key. Aims: investigate components of facilitation associated with successful implementation of the CSNAT intervention across 36 palliative care services. Methods: Qualitative: Interviews three and six months post-CSNAT implementation with 38 practitioners acting as CSNAT 'champion' (internal facilitation) in 32 services. Researcher field notes collected from teleconference support sessions with 'champions' (external facilitation). Results: Successful implementation of the CSNAT intervention was associated with: a teamwork approach to facilitation; the 'lead champion' having a leadership role in the service e.g. team manager; presenting a clear rationale why a change in practice was needed; reviewing progress and making changes to overcome identified barriers; 'champions' having good communication skills and authority to make changes. Aspects of context which constrained facilitation included the need to establish a new carer record, and organisational changes e.g. budget cuts, and a culture focused on the patient. Management support assisted with facilitation efforts. Conclusions: Establishing a team of practitioners to lead facilitation of the CSNAT intervention and regularly review implementation progress, is recommended to help ensure implementation success. References: Ewing G, Brundle C, Payne S, Grande G. The Carer Support Needs Assessment Tool (CSNAT) for use in palliative and end-of-life care at home: A validation study. J Pain Symptom Manage 2013;46 (3):395–405 Ewing G, Grande G. Development of a Carer Support Needs Assessment Tool (CSNAT) for end-of-life care practice at home: A qualitative study. Palliat Med 2013;27 (3):244–256 Ewing G, Austin L, Diffin J, Grande G. The Carer Support Needs Assessment Tool: A person centred approach to carer assessment and support. Br J Community Nurs 2015;20 (12):580–584